REGIONAL TOURISM AUTHORITY AND FACTORS AFFECTING IT (Marketing Journal, 2025)
This article analyzes the essence of regional tourism potential and the key factors influencing its development. It highlights the role of tourism in the global economy, emphasizing the importance of natural, historical -cultural, infrastructural, and socio - economic resources. Special attention is given to Uzbekistanʼs tourism potential, the recent growth in tourist arrivals, and the contribution of handicrafts and gastronomic tourism. The study also examines the impact of tourism on regional economic growth , sustainable development, and provides practical recommendations for enhancing the tourism sector.
Keywords: Tourism potential; regional development; natural resources; cultural heritage; infrastructure; tourist flow; handicrafts; gastronomic tourism; sustainable tourism; economic impact. 319